2006
DOI: 10.1002/pen.20528
|View full text |Cite
|
Sign up to set email alerts
|

New clay-reinforced nanocomposites based on a polycarbonate/polycaprolactone blend

Abstract: New clay‐reinforced polymer nanocomposites based on poly(carbonate of bisphenol A) (PC)/poly(caprolactone) (PCL) blends have been obtained by mixing PC with minor amounts of PCL in which a widely dispersed organically modified montmorillonite (OMMT) was present. Upon the addition of PCL/OMMT, the Tg of the matrix and the viscosity of the nanocomposites decreased and therefore processability increased. This was attributed to both the presence of PCL and the migration of some surfactant to the polymeric matrix. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 39 publications
4
34
0
Order By: Relevance
“…The opposite effect -that is, a decrease in the T g of the matrix in presence of OMMT -has been observed in PA6, [52] polyamide 11, [53] poly(methyl methacrylate) [54] and polycarbonate; [55] this was attributed to a migration of the surfactant during melt mixing, resulting in a plasticizing effect. [45,55] The existence [46] of a thin interface layer that tends to enhance the segmental dynamics of the polymer chains and to lower the T g has been also found.…”
Section: Phase Structurementioning
confidence: 93%
See 2 more Smart Citations
“…The opposite effect -that is, a decrease in the T g of the matrix in presence of OMMT -has been observed in PA6, [52] polyamide 11, [53] poly(methyl methacrylate) [54] and polycarbonate; [55] this was attributed to a migration of the surfactant during melt mixing, resulting in a plasticizing effect. [45,55] The existence [46] of a thin interface layer that tends to enhance the segmental dynamics of the polymer chains and to lower the T g has been also found.…”
Section: Phase Structurementioning
confidence: 93%
“…[45,55] The existence [46] of a thin interface layer that tends to enhance the segmental dynamics of the polymer chains and to lower the T g has been also found.…”
Section: Phase Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Hitherto many works have been reported on the preparation and characterization of PC/clay and PC alloy/clay nanocomposites (PCNs). [4][5][6][7][8][9][10][11][12][13][14][15] The effect of clay loading on the mechanical behavior and melt state linear viscoelastic properties of intercalated PC nanocomposites was investigated by Alex J. Hsieh et al 16 They observed that these nanocomposites also exhibited a significant decrease in the extent of tensile elongation and ductility with respect to the nanoclay incorporation. A concomitant decrease in the rheological properties at high frequencies was also observed, and was consistent with the lowering of the molecular weight of PC, particularly near or above the percolation threshold of nanoclay.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of PCL four methodologies have been used to prepare nanocomposites of PCL namely, in-situ polymerization 23,[121][122][123][124][125] , solution casting 126 , melt mixing 19,[127][128][129][130][131][132][133][134][135] and a master batch method.…”
Section: 4146mentioning
confidence: 99%